2018
DOI: 10.1177/0044118x18768115
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Viewing Online Extremism Among America’s Youth

Abstract: Exposure to hate material is related to a host of negative outcomes. Young people might be especially vulnerable to the deleterious effects of such exposure. With that in mind, this article examines factors associated with the frequency that youth and young adults, ages 15 to 24, see material online that expresses negative views toward a social group. We use an online survey of individuals recruited from a demographically balanced sample of Americans for this project. Our analysis controls for variables that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 40 publications
4
34
0
3
Order By: Relevance
“…In our study, we found that the more time youth spent online the more likely they were to be exposed to hate in the online space. This result is consistent with the previous literature [ 29 , 34 , 35 ]. Not surprisingly, communicating with strangers online was associated with an increased risk of being exposed to hate.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In our study, we found that the more time youth spent online the more likely they were to be exposed to hate in the online space. This result is consistent with the previous literature [ 29 , 34 , 35 ]. Not surprisingly, communicating with strangers online was associated with an increased risk of being exposed to hate.…”
Section: Discussionsupporting
confidence: 94%
“…In 2011, a US-based national study demonstrated that amount of general technology use and age are predictive factors for almost all technology-based violent experiences and exposures [ 32 ]. Recent research in the US has identified various socio-demographic, psychological, and behavioral factors that may put an individual at risk of exposure to hate online, such as young age, white race, male gender, level of education, online victimization, low trust in government, and time spent on the internet [ 34 , 35 ]. Such risk factors provide invaluable information on a pernicious phenomenon that has persisted at high levels over the past decade in the US.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we found that the more time youth spent online the more likely they were to be exposed to hate in the online space. This result is consistent with previous literature [24][25][26]. Not surprisingly, communicating with strangers online was associated with increased risk of being exposed to hate.…”
Section: Discussionsupporting
confidence: 93%
“…As such, it is important to understand who are the most vulnerable to such exposure, so to equip them with the requisite knowledge to critically assess the material they may come across while online. Recent research has identified various psychological and behavioral factors that may put an individual at risk of exposure to hate online, such as: race, level of education, victimization, weak family attachment, low trust in government, and time spent on the internet [24][25][26]. This study seeks to contribute to this body of research focusing on the understanding of the predictors of youth's exposure to online hate by exploring the role of demographic characteristics, attitudes, risk perceptions and online behaviors.…”
Section: Introductionmentioning
confidence: 99%